2018
DOI: 10.1155/2018/3234970
|View full text |Cite
|
Sign up to set email alerts
|

Oral Hygiene Practices among Saudi Arabian Children and Its Relation to Their Dental Caries Status

Abstract: Dental caries is one of the most common preventable diseases occurring among children. The aim here is to survey the oral hygiene practices that are commonly followed by Arab children and to see its relationship with their dental caries status. A cross-sectional study with multistage random sampling technique was conducted. Sociodemographic data and information on oral hygiene practices like use of toothbrush, dental floss, siwak, frequency of brushing along with number of snack between meals per day, and cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 16 publications
3
21
2
Order By: Relevance
“…The overall incidence of dental caries, plaque and gingival bleeding in the studied population was found to be significantly high in the current study, consistent with the findings of previous research conducted in Saudi Arabia across several cities, including Dammam, Tabuk, Riyadh and Jeddah [5][6][7][8][10][11][12]. This might indicate that dental caries and periodontal disease in Saudi Arabia are not treated regularly, similar to conditions in several developing countries [22,23].…”
Section: Advances In Dentistry and Oral Health Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The overall incidence of dental caries, plaque and gingival bleeding in the studied population was found to be significantly high in the current study, consistent with the findings of previous research conducted in Saudi Arabia across several cities, including Dammam, Tabuk, Riyadh and Jeddah [5][6][7][8][10][11][12]. This might indicate that dental caries and periodontal disease in Saudi Arabia are not treated regularly, similar to conditions in several developing countries [22,23].…”
Section: Advances In Dentistry and Oral Health Discussionsupporting
confidence: 89%
“…and 0.66, respectively [11]. Additionally, gingivitis was seen to be pervasive in Saudi adults aged 18-40 years (n = 385, 100%), with a mean gingival index (GI) score of 1.68±0.31, indicating moderate gingival inflammation [12].…”
Section: Advances In Dentistry and Oral Healthmentioning
confidence: 99%
“…Another research conducted on oral hygiene practices of 12 -13 years old school children supported our findings, DMFT was higher for cases who brush their teeth irregularly than cases who brush their teeth once or twice a day [25]. In a cross-sectional study performed on a sample of 658 children, aged 10 -14 years, the frequency of tooth cleaning was shown as; 19.3% once a week, 38.5 few times a week, 32.6 once a day, other 9.6 where the prevalence of dental caries was 47.4%.…”
Section: Discussionsupporting
confidence: 84%
“…The high prevalence of school children with poor teeth condition observed in the current study was similar to the reports from other developing [19] as well as developed nations [20] among children of same age range. However, there are no results from similar age group in Jazan region for comparison, but studies conducted in much younger children have also shown high prevalence of clinically examined tooth decay [8,9,21]. Further, results from the current study had revealed that both male and female children have quite often experienced toothache, and this may subsequently affect their daily activities [22] and also increase the possibility of school absenteeism [23].…”
Section: Discussionmentioning
confidence: 54%